Reflexões como preceptora na formação inicial de professores com o Programa Residência Pedagógica, Geografia, UFSM - Fagan, Elvani da Rocha (2024)
This work addresses the initial training of teachers, the graduates of the undergraduate course who participated in the Pedagogical Residency Program, Geography Subarea, UFSM, and were assigned to the field school Colégio Estadual Profª Edna May Cardoso. The author of this work participated as a preceptor teacher and internship supervisor in all three editions of the program, which contributed to her continued professional development. The PRP was a policy that supported the initial training of undergraduate students in teaching, contributing to the education of these professionals. In this way, the reports submitted by the residents at the end of each edition were analyzed in order to identify the challenges they faced in their initial training, as well as to highlight positive aspects of the pedagogical practices carried out. The PRP facilitated weekly interaction between students in teacher training programs, teachers in basic education schools, and UFSM professors, enhancing the quality of teaching practices for all involved. The final product proposed is a Photo Book, consisting of photos and records of the residents' memories, titled "Geography Memories in the Pedagogical Residency, UFSM, 2018 to 2024," serving as a way to express the importance that the PRP had in the initial training of geography teachers.